Work Engagement As A Mediator Linking Person-Job Fit, Perceived Training Benefit, And Self-Efficacy To Employee Resilience Among Heavy Equipment Mechanics - Kahvi Febriana Taufiq; Rimin Saputra; Primananda Adytya; Agustian B. Prasetya (Green Publisher Indonesia, 2026)
The coal mining industry is a high-risk work sector that demands high psychological resilience from its workers, including heavy equipment mechanics. Resilience is the key ability to survive, adapt, and remain productive under extreme work pressure. This study aims to examine the influence of Person-Job Fit (PJF), Perceived Training Benefit (BEN), and Self-Efficacy (SE) on Resilience (RES), with Work Engagement (WE) as a mediating variable. This study uses a quantitative approach with convenience sampling techniques on 301 heavy equipment mechanics working in the coal mining industry. Data were collected through a questionnaire survey and analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. The results of the study show that PJF and SE have a positive and significant direct influence on RES. In contrast, BEN does not have a direct effect on RES, but shows significant influence indirectly through WE mediation. All three independent variables—PJF, BEN, and SE—also had a significant effect on WE, which in turn increased RES. These findings confirm that WE plays an important mediating role in strengthening the relationship between individual resources and job resilience. The practical implications of these results encourage organizations to improve job suitability, training effectiveness, and employee self-confidence as strategies for building psychological resilience in challenging work environments.